2016
DOI: 10.1136/bmjopen-2015-008391
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair or open repair for ruptured abdominal aortic aneurysm: a Cochrane systematic review

Abstract: ObjectivesEmergency endovascular aneurysm repair (eEVAR) may improve outcomes for patients with ruptured abdominal aortic aneurysm (RAAA). The study aim was to compare the outcomes for eEVAR with conventional open surgical repair for the treatment of RAAA.SettingA systematic review of relevant publications was performed. Randomised controlled trials (RCTs) comparing eEVAR with open surgical repair for RAAA were included.Participants3 RCTs were included, with a total of 761 patients with RAAA.InterventionsMeta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…The three large multi-centre trials concluded that early mortality rates (30-day mortality or in-hospital mortality) following treatment for rAAAs are no better with EVAR than with OR (Table 1) [21,33,35]. A Cochrane systematic review and metaanalysis involving two of the major RCTs and the one pilot trial found no difference in early mortality between EVAR and OR (pooled odds ratio 0.91, 95% CI: 0.67-1.22; P=0.52) [15]. A further meta-analysis incorporating the data from the three multi-centre RCTs corroborated these findings (pooled odds ratio 0.88, 95% CI: 0.66-1.18; P=0.84) [36].…”
Section: Mortality Rate Differences Between Endovascular Repair and Omentioning
confidence: 99%
See 2 more Smart Citations
“…The three large multi-centre trials concluded that early mortality rates (30-day mortality or in-hospital mortality) following treatment for rAAAs are no better with EVAR than with OR (Table 1) [21,33,35]. A Cochrane systematic review and metaanalysis involving two of the major RCTs and the one pilot trial found no difference in early mortality between EVAR and OR (pooled odds ratio 0.91, 95% CI: 0.67-1.22; P=0.52) [15]. A further meta-analysis incorporating the data from the three multi-centre RCTs corroborated these findings (pooled odds ratio 0.88, 95% CI: 0.66-1.18; P=0.84) [36].…”
Section: Mortality Rate Differences Between Endovascular Repair and Omentioning
confidence: 99%
“…More specifically, participants who are haemodynamically stable are often assigned to EVAR, introducing a well-defined selection bias [42]. While there is an accompanying body of observational research failing to reveal any early-mortality benefit in utilising an endovascular approach [15,31,36,40,[43][44][45], there are virtually no literature items reporting EVAR as a more morbid curative approach [37]. So while there is no high-level evidence from randomised trials supporting EVAR over OR from an early mortality perspective [15,36], the trends within observational research favour the former.…”
Section: Development Of the Evidence-basementioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis [2] screened for all randomised controlled trials comparing EVAR to open repair in ruptured AAA using the Cochrane central register. Most studies were retrospective case-nested control studies (n = 10) or prospective observational studies (n = 5).…”
Section: Evar In Ruptured Abdominal Aneurysmsmentioning
confidence: 99%
“…Although a fi nal conclusion could defi nitely not be drawn yet in elective cases, it has been assumed that the benefi ts of EVAR must become even more obvious in patients with ruptured AAA. This subgroup of patients is usually in a critical clinical condition, suff ering from a high early mortality of about 60 -80 % [1,2]. Therefore, a less invasive procedure should result in more favourable outcomes.…”
mentioning
confidence: 99%